Tentang Rumus Induksi Matematika - M. Yusuf Syaifuddin; Siti Zahidah, S.Si, M.Si; Eridani (Contemporary Mathematics and Applications (ConMathA), 2023)
This paper presents various forms of induction formulas and at the same time proves the equivalence of these formulas by proving that some of these formulas are equivalent to the Well-Ordering Principle which applies to natural number set.